Small Interfering RNA Targeting Nerve Growth Factor Alleviates Allergic Airway Hyperresponsiveness - Yi-Lien Chen; Hsin-Ying Huang; Chen-Chen Lee; Bor-Luen Chiang (Elsevier, 2014)
Airway hyperresponsiveness is the hallmark of allergic asthma and caused by multiple factors. Nerve growth factor (NGF), a neurotrophin, is originally known for regulation of neural circuit development and function. Recent studies indicated that NGF contributes to airway hyperresponsiveness and pathogenesis of asthma. The objective of this study is to develop a small interfering RNA against NGF to attenuate airway hyperresponsiveness and further elucidate the underlying mechanism. In a murine model of allergic asthma, the ovalbumin-sensitized mice were intratracheally delivered small interfering RNA against NGF or administered an inhibitor targeting NGF receptor, tropomyosin-related kinase A, as a positive treatment control. In this study, knockdown NGF derived from pulmonary epithelium significantly reduced airway resistance in vivo. The levels of NGF, proinflammatory cytokines and infiltrated eosinophils in airway were decreased in small interfering RNA against NGF group but not in tropomyosin-related kinase A inhibitor and mock siRNA group. Furthermore, induction of neuropeptide (substance P) and airway innervation were mediated by NGF/tropomyosin-related kinase A pathway. These findings suggested that NGF targeting treatment holds the potential therapy for antigen-induced airway hyperresponsiveness via attenuation of airway innervation and inflammation in asthma.